Autoantibodies to neuronal antigens in children with new‐onset seizures classified according to the revised ILAE organization of seizures and epilepsies. Issue 12 (23rd October 2013) - Suleiman, Jehan; Wright, Sukhvir; Gill, Deepak; Brilot, Fabienne; Waters, Patrick; Peacock, Ken; Procopis, Peter; Nibber, Anjan; Vincent, Angela; Dale, Russell C.; Lang, Bethan
Summary Purpose Potentially pathogenic autoantibodies are found increasingly in adults with seizure disorders, including focal seizures and those of unknown cause. In this study, we investigated a cohort of children with new‐onset seizures to see whether there were autoantibodies and the relationship to any specific seizure or epilepsy type. Methods We prospectively recruited 114 children (2 months to 16 years) with new‐onset seizures presenting between September 2009 and November 2011, as well as 65 controls. Patients were clinically assessed and classified according to the new International League Against Epilepsy (ILAE) organization of seizures and epilepsies classification system. Sera were tested for autoantibodies to a range of antigens, blind to the clinical and classification details. Key Findings Eleven (9.7%) of 114 patients were positive for one or more autoantibodies compared to 3 of 65 controls (4.6%, p = ns). Patients had antibodies to the voltage‐gated potassium channel (VGKC) complex (n = 4), contactin‐associated protein‐like 2 (CASPR2) (n = 3), N‐methyl‐d‐aspartate receptors (NMDARs) (n = 2), or VGKC‐complex and NMDAR (n = 2). None had antibodies to glutamic acid decarboxylase, contactin‐2, or to glycine, 2‐amino‐3‐(3‐hydroxy‐5‐methyl‐4‐isoxazolyl) propionic acid (AMPA), or γ‐aminobutyric acid B receptors. Ten of these 11 patients were classified as having epilepsy according to the new ILAE organization of seizures and epilepsy. Although, there were no significant differences in the demographic and clinical features between antibody‐positive and antibody‐negative patients, the classification of "unknown cause" was higher in the antibody positive (7/10; 70%) compared with the antibody negative subjects (23/86; 26.7%; p = 0.0095, Fisher's exact test). Furthermore, four of these seven patients with epilepsy (57.1%) were classified as having predominantly focal seizures compared with 12 of the 86 antibody‐negative patients (13.9%; p = 0.015). Significance Because autoantibodies were more frequent in pediatric patients with new‐onset epilepsy of "unknown cause, " often with focal epilepsy features, this group of children may benefit most from autoantibody screening and consideration of immune therapy.